Editorial - Fischer, Gerhard; Alvarez-Herrera, Javier Giovanni; Flórez Faura, Rafael (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2015)
Editorial